Perfil antropométrico dos praticantes de jiu-jitsu da cidade de Pedras de fogo-PB - Silva, Thomás Barbosa Ornilo da (2021)
The details of the anthropometric profile of athletes in a given sport is essential for understanding sports requirements, training organization, and performance prediction. The study aimed to describe the anthropometric profile of Jiu-Jitsu practitioners in the city of Pedras de Fogo-PB. The research has descriptive and developmental characteristics with a cross-sectional design. The sample consisted of 12 male Jiu-Jitsu athletes, with minimum graduation in blue belt and minimum age of 16 years. The measurements collected were: body mass, height, arm span, eight skin folds (bicipital, tricipital, subscapular, iliac crest, supraspinale, abdominal, thigh, and calf), seven perimeters (arm relaxed, arm flexed and tensed girth, forearm girth, waist girth, hips girth, thigh middle, and calf girth) and four bone diameters (humerus breadth, bi styloid breadth, femur breadth, and malleolar breadth). From there, body components (BMI, % of fat, % of lean mass, % of muscle mass, % of bone mass), Muscle-Bone Index,Somatotype (endomorphy, mesomorphy and ectomorphy), and the Sum of skin folds ∑6 DOC. The measurements were made according to the methodology proposed by the International Society for the Advancement of Kineanthropometry (ISAK). The data obtained were statistically analyzed using the Excel® program and presented in mean, standard deviation (SD), and amplitude (minimum and maximum values). The comparisons of the averages of the athletes' somatotypes according to the fighting style were performed using GraphPad Prism 8.0.1® (Graphpad Software, San Diego, CA, USA), using a Student t Test for unpaired samples, with a pre-established significance of 5% (p <0.05). The athletes presented a predominance of the mesomorphic component. When comparing the somatotypes, according to the fighting style, the pass fighters expressed a significantly greater muscular aspect than the guard fighters.